2020
DOI: 10.1088/1755-1315/614/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

An overview of hydrogen-rich gas production from biomass by using thermal technologies

Abstract: Studies on the production of hydrogen energy are at the forefront of reducing the dependence on fossil fuel energy. This work is a brief summary of hydrogen production systems especially in a supercritical water environment. Hydrogen production by the gasification of organic wastes in a supercritical water environment has been preferred more than other methods in recent years. In this study, the common biomass resources used for the hydrogen production have been explored, evaluating their properties. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Biomass gasification involves a thermochemical process at high temperatures (~900 • C) and low pressure. The main steps include drying the feedstock, pyrolysis of the feedstock, and a reaction part including oxidation, reduction, and cracking [67][68][69]. The products are carbon monoxide, carbon dioxide, methane, and hydrogen.…”
Section: Biomass Gasificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass gasification involves a thermochemical process at high temperatures (~900 • C) and low pressure. The main steps include drying the feedstock, pyrolysis of the feedstock, and a reaction part including oxidation, reduction, and cracking [67][68][69]. The products are carbon monoxide, carbon dioxide, methane, and hydrogen.…”
Section: Biomass Gasificationmentioning
confidence: 99%
“…[69][70][71]. The main drawback of this method is releasing tar that should be removed from the syngas, which is expensive and reduces the overall efficiency [67]. Over the past years, many studies have been carried out to optimize the operating conditions.…”
Section: Biomass Gasificationmentioning
confidence: 99%
“…One common methodology utilizes backcasting, which first identifies desired transition goals or targets as an endpoint and assesses the necessary transition steps and intervention pathways needed to achieve policy goals (Giurco et al 2011). Other research has demonstrated sustained improvement of hydrogen production efficiency (Kaskun and Kayfeci, 2018, Kaskun 2020 and noted economic synergies and greenhouse gas reduction benefits for hydrogen production in regions with substantial wind capacity (Scolaro and Kittner 2022). However, just one study has examined the transition to hydrogen production potential in Latin America, and has done so primarily through an economic lens (Moreira dos Santos et al 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have large specific surface areas, highly porous and hollow structures, low density, excellent mechanical properties, good thermal stability, tunable surface chemistry, non‐corrosive properties, and other distinctive chemical and physical properties. Thus, CNTs have been widely used in many fields as hydrogen storage materials, 11–13 adsorption materials, 14,15 nano‐filling materials, 16 and electrode materials 17 . Recently, a large number of studies have confirmed that CNTs show strong potential as high‐efficiency adsorbents for the adsorption and degradation of various pollutants such as metallic ions, 18–21 organic dyes, 22,23 and other harmful organic compounds 24 .…”
Section: Introductionmentioning
confidence: 99%